A prospective study of the prevalence of undiagnosed coeliac disease in laboratory defined iron and folate deficiency. Issue 10 (1st October 2002) - Howard, M R; Turnbull, A J; Morley, P; Hollier, P; Webb, R; Clarke, A
Abstract : Aims: To determine the prevalence of coeliac disease in a group of patients in the community who have been shown in the laboratory to have iron and/or folate deficiency. To assess the cost efficiency of this laboratory based case finding strategy. Methods: The study was undertaken in a large general hospital in the UK serving a population of 300 000. Three hundred and thirty three eligible patients with iron and/or folate deficiency were identified and contacted over an 18 month period. Case finding was by testing for coeliac disease using serological methods and subsequent histological confirmation. Results: Of the 333 eligible and contactable patients with iron and/or folate deficiency, 258 (77%) consented to coeliac disease antibody testing. Twenty eight patients (10.9%) were positive for coeliac disease antibodies. Of these, 24 patients proceeded to endoscopy and biopsy, resulting in 12 cases of histologically confirmed coeliac disease (4.7% (95% confidence interval, 2.1% to 6.8%) of patients tested for coeliac disease antibodies). Conclusions: This laboratory based methodology detected a considerable number of new coeliac disease cases in the community. Many of these patients did not present with clinical findings suggestive of malabsorption and might not otherwise have been diagnosed. Laboratory based methodologies should be considered in conjunction with other strategies for the early identification and treatment of coeliac disease.